Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1136/annrheumdis-2013-204902
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy, radiographic and safety findings through 5 years of subcutaneous golimumab treatment in patients with active psoriatic arthritis: results from a long-term extension of a randomised, placebo-controlled trial (the GO-REVEAL study)

Abstract: ObjectivesAssess golimumab's long-term efficacy/safety in psoriatic arthritis (PsA).MethodsAdults with active PsA (≥3 swollen and tender joints, active psoriasis) were randomly assigned to subcutaneous placebo, golimumab 50 mg, or golimumab 100 mg every 4 weeks (q4wks) through wk20. All patients received golimumab 50 mg or 100 mg q4wks from wk24 forward. Methotrexate was allowed and taken by approximately half the patients. Findings through 5 years are reported herein. Efficacy assessments included ≥20% improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 7 publications
4
97
0
6
Order By: Relevance
“…As reported previously 10, 126 of 405 patients (31.1%) discontinued study treatment through week 252, with the most common reasons for study agent discontinuation being adverse events and unsatisfactory therapeutic response. Baseline disease characteristics, as well as the proportions of patients reporting MTX use at baseline, were generally consistent among randomized treatment groups (see Supplementary Table 1 available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr.22576/abstract) and were generally consistent between patients who continued and discontinued study agent (data not shown).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…As reported previously 10, 126 of 405 patients (31.1%) discontinued study treatment through week 252, with the most common reasons for study agent discontinuation being adverse events and unsatisfactory therapeutic response. Baseline disease characteristics, as well as the proportions of patients reporting MTX use at baseline, were generally consistent among randomized treatment groups (see Supplementary Table 1 available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr.22576/abstract) and were generally consistent between patients who continued and discontinued study agent (data not shown).…”
Section: Resultssupporting
confidence: 58%
“…The phase III, randomized, double‐blind GO‐REVEAL trial of 405 PsA patients treated with golimumab for up to 5 years 7, 8, 9, 10 provided an opportunity to retrospectively assess the implications of achieving a treatment goal, namely MDA, that is more rigorous than the typical objectives of therapeutic studies in PsA. The composite PsA MDA criteria have been preliminarily validated in both observational and interventional trial cohorts 5, 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our current study was a pooled analysis of previously collected safety data from 5 large multicenter trials [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 , each of which was conducted according to the Declaration of Helsinki and the International Committee on Harmonisation Good Clinical Practices. Each of the phase 3 study protocols was approved by central or individual site institutional review boards/ethics committees, and all patients provided written informed consent prior to any study-related procedures.…”
Section: Methodsmentioning
confidence: 99%